Badania archeologiczne Rynku w Bieruniu Starym, woj. śląskie - Andrzejewski, Aleksander; Lewandowski, Marcin; Pietrzak, Janusz (Acta Universitatis Lodziensis. Folia Archaeologica, 2004)
Archaeological excavations on the area of the market place in Bieruń Stary were next stage of researches intended to lead to modernisation and rebuild of the market surface as well as rebuild and partial exchange of the terrain’s infrastructure. As a result of an agreement between a building company and the Preservation Service, after having informed the Investor, the Town and Commune Council in Bieruń Stary, seven exploratory units of total 200 sq m have been marked out. They were located in places where earlier radar and electromagnetic investigations of the ground made with the SIR radar indicated disturbances in stratification. It suggested that archaeological features occurred there. The disturbances were interpreted as remains of a town hall, scales, other market buildings and surfaces hardening the market area (covering with wood, stone pavements). The excavations carried out on the market of Bieruń Stary have yielded considerable collection of artefacts. Together 5875 items have been found; the most numerous group (4565) was constituted by fragments of clay vessels. The frequency of each collection of artefacts in different exploratory units was various and the whole material can be treated as strongly shattered and secondary mixed to a great extent. The artefacts quite regularly saturated stratification of all the units except unit VII where barely 144 specimens have been found. As a result of the excavations it has been stated that in the areas in point there are no remains that could be connected with the town functioning from its location at the end of the 14th till the 17th century. It is possible that the town originally had a different location and different directions of development and no sooner than after the great fire in 1677 a new town regulation took place. Great probability of this hypothesis is well founded by the fact that the oldest traces of the market usage only come from the 2nd half of the 17th century. Also all the discovered relics of wooden buildings are dated to the years immediately after the fire. As far as inter-market buildings are concerned, in the northern part of the market (in a place indicated as a result of the radar investigation) relics of the south-western comer of a building have been revealed. We believe that, with great probability, it can be assumed that it is a remnant of the town scales. In the terrain it manifests in a layer of broken stone being a foundation of inconsiderably preserved comer wall beam. The relic can be preliminarily dated to the 19th century. Unfortunately no other remains of the inter-market building area have been found although their occurrence is suggested by the SIR radar investigation. Similarly, relics of the stone paved road have not been found. Only the presence of earthen layers from the 2nd half of the 17th - the beginning of the 20th century. In the central part of the market, in the place suggested by the SIR investigation, relics of the town hall have not been found. To be quite truthful, there are some relics of an archaeological object, but its fragmentary state excludes any far-reaching conclusions. We think that there is an interesting situation in the south-western frontage of the market where relics of its older, southern frontage have been registered. It should be dated to the period from the 2nd half of the 17th to the end of the 18th century. It was shifted about 13 metres north of the present frontage. A wooden pavement once coming under the arcades has been registered, which is showed by relics of posts placed in the surface of the pavement. Before padding beams were laid, the surface of the market had been strengthened by fascine. Whereas after the liquidation of the original building line and enlargement of the market to its present size its surface (at least in the region under consideration) was paved with broken limestone. It probably happened at the end of the 18th or at the beginning of the 19th century. In the surface the presence of a gutter (a sewer canal) made of different kinds of coniferous wood has been stated. At the beginnings of the 20th century the rebuild of the market surface took place. In the area under investigation it was carefully paved with broken limestone, what undoubtedly contributed to the town’s aesthetics, but unfortunately at the opportunity destroyed the older layers.